2021
DOI: 10.1037/fam0000838
|View full text |Cite
|
Sign up to set email alerts
|

Learning to let go: Parental over-engagement predicts poorer self-regulation in kindergartners.

Abstract: Responsive parenting and parental scaffolding have been shown to foster executive functions (EFs) and self-regulation skills in young children, but could too much parental directive engagement be counterproductive? To answer this question, we examined parental responses when children were demonstrating active on-task behaviors in a community sample of 102 dyads. We measured the time that parents spend actively guiding children's behavior relative to following the child's lead and created a measure of parental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 48 publications
(90 reference statements)
0
10
0
1
Order By: Relevance
“…Additionally, while healthy amounts of cognitive stimulation may be important for the development of the VVS, EF, and academic achievement, a recent study suggests that mothers who were randomly assigned to teach their child something not only increased their cognitive stimulation but also increased intrusiveness ( King et al, Under Review ). Recent work also demonstrates that high greater parental intrusiveness is linked to lower self-regulation and performance on EF tasks in children ( Obradivic et al, 2021 ). Therefore, future work should focus on a more nuanced understanding of the circumstances under which cognitive stimulation is beneficial for cognitive and neural development.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, while healthy amounts of cognitive stimulation may be important for the development of the VVS, EF, and academic achievement, a recent study suggests that mothers who were randomly assigned to teach their child something not only increased their cognitive stimulation but also increased intrusiveness ( King et al, Under Review ). Recent work also demonstrates that high greater parental intrusiveness is linked to lower self-regulation and performance on EF tasks in children ( Obradivic et al, 2021 ). Therefore, future work should focus on a more nuanced understanding of the circumstances under which cognitive stimulation is beneficial for cognitive and neural development.…”
Section: Discussionmentioning
confidence: 99%
“…Research has indicated that such arbitrary control can cause a child to be a “rebel” (Van Petegem et al, 2015). Children do not show committed compliance or internalization of parents’ demands; instead, they exhibit increasingly negative affect and resistant behaviors (Grolnick & Pomerantz, 2009; Obradovic et al, 2021). Their defiance toward parents can extend to peer interactions, where, for example, they break rules (McDowell & Parke, 2005) and bully (Georgiou et al, 2013).…”
Section: Parenting Styles and Child Externalizing Behaviorsmentioning
confidence: 99%
“…Sometimes parental involvement such as involvement in PTA and volunteering inside and outside of the classroom can be the parent exercising tight social control over their children, whereas such parental involvement minimizes children’s disruptive behavior in school, it may have little effect on cognitive development (Domina, 2005). On the other hand, parental involvement enhances students’ behavioral and academic performance when parents give children room to develop autonomy and self-regulate (Obradović et al, 2021).…”
Section: Introductionmentioning
confidence: 99%